Exploration of Lipase Enzyme from Soil through Metagenomic Approach - Sumarsih, Sri; Baktir, Afaf; Andina, Budi Putri Ayu (UNEJ e-Proceeding, 2014)
This research aimed to explore lipase enzyme from soil through metagenomic approach. The DNA was extracted directly from the topsoil and river sediment by SDS-based lysis method. The soil genomic DNA was sheared into approximately 40-kb fragments The construction of genomic library was carried out by cloning the fragment DNA intoÂ fosmid pCC2FOS vector and host E. coli EPI300-T1R accordance with the protocols of CopyControlâ¢ Fosmid production library kit. Screening of lipase-producing clones was performed based on its lipolytic activity using Luria-Bertani agar plate 12.5 Âµg/ ml chloramphenicol, 10 Âµg/ml Rhodamine B and 1 % olive oil as a substrate. The assay plates were incubated at 550 C. The lipolytic activity was identified as an orange around colonies. There were 5 (five) clones of 32 screened-clones that expressed lipolytic activity. The next research will characterize the enzyme and determine the sequence of the enzyme-encoding gene. Keywords: Lipase, soil, metagenomic, fosmid vector, pCC2FOS, E. coli EPI300-T1R